Pelaksanaan Manajemen Data Kesekretariatan dalam Menunjang Manajemen Pastoral Paroki - Zakeus Daeng Lio; Irawati Teris (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2019)
The purpose of this study is to describe the implementation of secretarial data management in supporting the pastoral management of the parish in the Sacred Heart of Jesus Mangkupakas Parish. This study uses a descriptive qualitative research approach with data collection techniques used are observation, interviews, and documentation studies. The results showed that the implementation of six patterns of secretarial data management activities, namely gathering, recording, managing, organizing, sending, and storing data, was instrumental in supporting the four main steps of parish pastoral management namely planning, organizing, leadership and supervision. The data of the faithful that is done well, effectively and efficiently and the vision of the Parish Church is achieved is the result of collaboration and hard work of both the Parish Priest, the Parish Pastoral Council, the Territorial Pastoral Council and the Base Community Pastoral Council supported by the involvement of the people in the parish pastoral work in the Sacred Heart of Jesus Mangkupalas Parish, by showing good planning, clear organization, responsible leadership, and supervision and evaluation in every pastoral activity carried out.